Local government policy evolution in New Zealand: radical reform and the ex post emergence of consensus or rival advocacy coalitions - Wallis, Joe; Dollery, Brian (2001)
Between 1984 and 1993 New Zealand reformers followed a top-down strategy designed to minimize the opportunity for resistors to affect the reform process and preclude the ex post emergence of a stable alignment of rival advocacy coalitions. The evolution of the local government policy debate since the implementation of radical reform in 1989 suggests that these strategic goals may be more difficult to achieve than at first thought. The quest to make local government more efficient and democratic by making it more accountable has given way to a `minimalist-activist' controversy over the comparative institutional advantage of local authorities and the role of trust in their relations with central government that has the potential to contribute to the eclipse of the post-reform consensus and the emergence of a `advocacy coalition structure'. - Reproduced
Keywords: Local government